Analysis of Behavior and Treatment of Mask Waste Impact of the Covid-19 Pandemic and Its Impact on the Environment - Alim Andini Razes, Widita; Setyono, Prabang; Hawali Abdul Matin, Hashfi (Diponegoro University, 2024)
The pandemic caused by Covid-19 has had various impacts on people's lives. One of these impacts is the use of masks when carrying out outdoor activities. Most people use disposable masks, so the amount of disposable mask waste has increased during the pandemic and post-pandemic. This research aims to find out whether people process disposable mask waste during the pandemic until post-pandemic. The research method was carried out using a non-probability sampling method using Google Form. Data analysis was carried out using Likert calculations and elasticity calculations. The results of the research show a decrease in people's behavior towards processing disposable mask waste during the pandemic to post-pandemic with E = 0.535, which means that people's behavior is inelastic.